Concomitant Gastrointestinal Stromal Tumor of the Stomach and Gastric Adenocarcinoma in a Patient with Billroth 2 Resection. (22nd December 2013) - Sista, Federico; Abruzzese, Valentina; Schietroma, Mario; Amicucci, Gianfranco
Abstract : Background . With this study we focus on the etiopathogenesis and on the therapy of the simultaneous occurrence of Gastric gastrointestinal stromal tumor (gGIST) and adenocarcinoma of the stomach in a patient with Billroth II gastric resection (BIIGR). We report the first case of this event and a review of the literature. Methods . A 70-year-old man with a BIIGR, affected by adenocarcinoma of the stomach, was successfully treated with total gastrectomy. The histological examination showed a gastric adenocarcinoma with a synchronous GIST sized 2 cm and S-100, CD117, and CD34 positive. The mutation of PDGFR gene was detected. Discussion . This tumor is a rare mesenchymal neoplasm of the gastrointestinal tract. Few cases of synchronous gastric adenocarcinoma and GIST are observed in the literature and no case in patients with BIIGR. Various hypotheses have been proposed to explain this occurrence. It is frequently attributed to Metallothioneins genes mutations or embryological abnormalities, but this has not been proven yet. We suggest a hypothesis about the etiopathogenesis of this event in a BIIGR patient. Conclusion . GIST may occur synchronously with gastric adenocarcinoma. This simultaneous occurrence needs more studies to be proven. The study of Cajal cells' proliferation signalling is crucial to demonstrate our hypotesis.